AN EXAMPLE OF STATISTICAL ANALYSIS USED IN STUDYING SPORTS PERFORMANCE IMPROVEMENT - Iuliana Carmen BĂRBĂCIORU; Eduard Robert SAKIZLIAN (Fiabilitate şi Durabilitate)
The purpose of this article is to present a mathematical model using dynamic data of athletes' performance in a particular sport. Where it is necessary to throw the ball, with the hand or racket, from the place or from the athlete's jump, certain parameters are analyzed. Aided by technology, coaches can make decisions that contribute to improving sports performance. Specifically, in this article we will present a program in MAPLE to be used in the normality analysis of data series for the improvement of sports performance.